2021
DOI: 10.3390/s21072573
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Comparison and Validation of Published Methods to Detect Turn Switch during Alpine Skiing

Abstract: The instant of turn switch (TS) in alpine skiing has been assessed with a variety of sensors and TS concepts. Despite many published methodologies, it is unclear which is best or how comparable they are. This study aimed to facilitate the process of choosing a TS method by evaluating the accuracy and precision of the methodologies previously used in literature and to assess the influence of the sensor type. Optoelectronic motion capture, inertial measurement units, pressure insoles, portable force plates, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A previous study already used lateral acceleration of the trunk to delimit linked turns in alpine skiing [33]. In this study, we wanted to follow this idea because of its high accuracy and precision [35]. However, for the present study, an accelerometer with a five times higher sampling frequency was used to clearly differentiate turn phases into the INI and STE IN+OUT phases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study already used lateral acceleration of the trunk to delimit linked turns in alpine skiing [33]. In this study, we wanted to follow this idea because of its high accuracy and precision [35]. However, for the present study, an accelerometer with a five times higher sampling frequency was used to clearly differentiate turn phases into the INI and STE IN+OUT phases.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of alpine skiing, it has been demonstrated that the TS point can be detected with the use of a single IMU through the inclination of the pelvis [16], or data based on the lateral acceleration of the trunk [33] or the angular velocity of the boot [34]. The latter two have been two of the most accurate and precise methodologies [35].…”
Section: Introductionmentioning
confidence: 99%
“…For further information regarding the wearable system, see Martínez et al (22). The turns were detected using the algorithm proposed previously by Martínez et al (29,30). The procedure utilized the mean angular velocity about the Z-axis (roll axis, pointing anteriorly) recorded from IMU's mounted on the upper posterior cuff of each ski boot.…”
Section: Physiological Datamentioning
confidence: 99%
“…To obtain the gray area in the center of the image, it is necessary to correctly distinguish the area and side length of the gray part [17] and take the position of the center as the coordinate center, which is taken as [p, q], and the formula of the central position is…”
Section: Preprocessing Of Extracting the Starting Action Of Snowboardmentioning
confidence: 99%